Influence of local thermal dissipation on electromigration in an Al thin-film line. (October 2016) - Li, Yuan; Lee, Hsin-Tzu; Saka, Masumi
Abstract: To improve the reliability of Al thin-film lines in integrated circuits, the influence of local thermal dissipation on electromigration (EM) was investigated. By performing current stressing experiments on Al thin-film lines with a special design, the unique distribution of hillocks/voids around four representative zones was found. The underlying mechanism was explained by investigating the corresponding atomic flux divergence according to finite element analyses. Such unique distribution of hillocks/voids, differing from the general EM phenomenon with hillocks at anode and voids at cathode, indicates the influence of local thermal dissipation induced by the voltage-measuring pads. Moreover, by changing the position of the voltage-measuring pads in the Al thin-film line, it was found that when the position of local thermal dissipation is farther from the center of the line, the EM resistance is higher. This finding provides a valuable insight for improving the EM resistance of Al thin-film lines and therefore enhancing the reliability of the corresponding devices. Highlights: Current stressing experiments were performed on Al thin-film lines with a special design. The unique distribution of hillocks/voids was identified, which indicates the influence of local thermal dissipation on EM. The mechanism was explored by analyzing the atomic flux divergence in the line based on FEA. The influence of the location of local thermal dissipation was also clarified.